Hypertension in obesity: A focus on individualized pharmacotherapy and the role of body composition, on behalf of the European Society of Hypertension Working Group on Diabetes and Metabolic Risk Factors and Working Group on Lifestyle, Cardiovascular Pharmacotherapy and Adherence - Christina Antza; Andrej Belancic; Jens Jordan; Alberto Esteban; Anna Oliveras Serrano; Ryan McNally; Panagiota Anyfanti; Jorie Versmissen; María S. Fernández‐Alfonso; Vasilios Kotsis; Thomas Weber; Alexandre Persu; et al. (British Journal of Clinical Pharmacology, 2026)
Hypertension in obesity represents a major global health challenge, closely linked to the global epidemics of obesity, type 2 diabetes and metabolic dysfunction. Excess adiposity contributes to elevated blood pressure through multiple, interrelated mechanisms, including activation of the renin–angiotensin–aldosterone system, sympathetic nervous system overactivity, insulin resistance, inflammation and adipokine dysregulation. Importantly, emerging evidence indicates that body composition plays a critical role in modulating hypertension risk, treatment response and cardiovascular outcomes. This article highlights the need for a more individualized pharmacotherapeutic approach to hypertension in people with obesity. While lifestyle modification and weight reduction remain essential, pharmacological treatment should be tailored to underlying pathophysiological drivers, such as volume expansion, neurohormonal activation and metabolic abnormalities. The potential different antihypertensive drug classes in hypertension related with obesity are also discussed. A precision medicine approach that incorporates body composition and metabolic risk factors may improve blood pressure control and decrease residual cardiovascular risk in this high‐risk population.